What is the impact of SOCS3, IL-35 and IL17 in immune pathogenesis of recurrent pregnancy loss? - Ozkan, Zehra Sema; Deveci, Derya; Simsek, Mehmet; Ilhan, Fulya; Risvanli, Ali; Sapmaz, Ekrem (Taylor & Francis Ltd, 2015)
Objective: To investigate the plasma levels of interleukin-4 (IL-4), IL-6, IL-10, tumor necrosis factor-alpha (TNF-alpha), interferon-gamma (IFN-gamma), transforming growth factor-beta (TGF-beta), IL-17, IL-35 and suppressor of cytokine signaling 3 (SOCS3) in the women with history of idiopathic recurrent pregnancy loss (RPL) and in the fertile controls. Methods: This study was conducted with 60 idiopathic RPL cases and 40 age-matched fertile controls. Mid-follicular plasma levels of IL-17, IFN-gamma, TNF-alpha, TGF-beta, IL-6, IL-4, IL-10, SOCS3 and IL-35 were assayed by an enzyme linked immunosorbent assay. Results: The mean age of RPL and control cases were 31.6 +/- 0.6 and 32.1 +/- 0.7 years, respectively. While plasma IL-35 and SOCS3 levels of RPL group were significantly lower than that of the control group; IFN-gamma, TNF-alpha, IL-4, IL-6, IL-10, IL-17 and TGF-beta levels of RPL group were significantly higher than that of the control group. The comparison of cytokine ratios between RPL and control groups indicated significantly high TNF-alpha/IL-10, TNF-alpha/IL-4, IFN-gamma/IL-10, IFN-gamma/IL-6 and IFN-gamma/IL-4 ratios in the RPL group. IL-35/IL-17 ratio was significantly low in the RPL group compared to that in the control group. Overstimulation of TNF-alpha presented moderate influence on recurrent miscarriage risk. Conclusion: Decreased SOCS3 and IL-35 plasma levels and increased Th1/Th2 cytokine ratios in RPL cases pointed out the supression of anti-inflammatory process and this supression might play an important role in the pathogenesis of idiopathic RPL.
Keywords: IL-17; IL-35; recurrent pregnancy loss; SOCS3; T helper